A CONCEPTUAL APPROACH TO BEAUTY THROUGH DINACHARYA - Fathima Noor; Rangannavar Santosh (International Journal of Applied Ayurved Research, 2020)
Cosmetology is the science of oscillation of appearance and mutation of beauty. Beauty is not just a source of joy, but also relaxes the mind. Beauty boost the individual's confidence. The increased demand of beautification is evident by magnitude of beauty competition, beauty parlours, a range of makeup items like creams, lotions, powder etc. Along with increased demand of beautification, the problems are also increasing which cause damage to Beauty or Personality due to changed life style and polluted atmosphere. Ayurveda, world’s oldest system of health deals with all aspect of human life. Ayurveda emphasizes on external and internal beauty. It can be enhanced by understanding and following basic guideline mentioned in Ayurveda in the form of Swasthavritta. In the Ayurvedic text there is importance of Dincharya i.e. daily regime which is said by Acharyas for human being to be healthy. There is Dincharya procedures for skin becoming healthy and for its good complexion and its texture Here it’s my petit effort to highlight Dinacharya as a restorative Intervention in cosmetology.